The Economic, Social and Cultural Development between the State of Israel and the Czech Republic - Tsybyktarov, Aldar; Dasan, Pramod; Bolotov, Ilya; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The goal of the thesis is to evaluate whether the international cooperation between the State of Israel and the Czech Republic has enriched the two countries. The work introduces the involved countries in the first chapter and briefly describes the history of the Czech-Israeli cooperation in the second. Quantitative economic indicators such as the balance and structure of trade or foreign direct investments between the involved countries can be found in the third chapter. The fourth chapter is about social and cultural cooperation -- here, qualitative data, obtained through personal interviews of representatives of the Embassy of the State of Israel in Prague is used. The fifth chapter introduces governmental and non-governmental institutions which promote cooperation in the described areas. The sixth chapter is dedicated to a brief prognosis of the Czech-Israeli cooperation. The final chapter, on the basis of collected data, aims to assess whether this international cooperation has benefited the citizens of both countries through economic growth, and, the growth of the value of the human capital which can be attained through education, social inclusion and cultural events.
Vedoucí práce: Pramod Dasan
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses